2020
DOI: 10.1016/j.fluid.2020.112762
|View full text |Cite
|
Sign up to set email alerts
|

Vapor-liquid equilibria, solid-vapor-liquid equilibria and H2S partition coefficient in (CO2 + CH4) at temperatures between (203.96 and 303.15) K at pressures up to 9 MPa

Abstract: Vapor-liquid equilibrium (VLE) measurements of the (CO2 + CH4) system are reported along seven isotherms at temperatures varying from just above the triple point to just below the critical point of CO2 at pressures from the vapor pressure of pure CO2 to approximately 9 MPa, including near-critical states. From these data, the critical locus has been determined and correlated over its entire length. The VLE data are correlated with the Peng-Robinson equation of state (PR-EoS), using a temperature-dependent bina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Zhang [20] conducted a phase simulation study of the coexistence systems of natural gas and water containing CO 2 and H 2 S, and conducted the sensitivity analysis of pressure, temperature, water content, and other factors. In the experiment of CO 2 -H 2 S coexistence systems, Theveneau [21] and Souza [22], have conducted phase equilibrium experiment of CO 2 -H 2 S-CH 4 system. Zhang [23] conducted a phase equilibrium experiment of CO 2 -H 2 S-crude oil system.…”
Section: Review On the Mechanism Of Co 2 Storage And Enhanced Gas Rec...mentioning
confidence: 99%
“…Zhang [20] conducted a phase simulation study of the coexistence systems of natural gas and water containing CO 2 and H 2 S, and conducted the sensitivity analysis of pressure, temperature, water content, and other factors. In the experiment of CO 2 -H 2 S coexistence systems, Theveneau [21] and Souza [22], have conducted phase equilibrium experiment of CO 2 -H 2 S-CH 4 system. Zhang [23] conducted a phase equilibrium experiment of CO 2 -H 2 S-crude oil system.…”
Section: Review On the Mechanism Of Co 2 Storage And Enhanced Gas Rec...mentioning
confidence: 99%
“…The vapour-liquid equilibrium (VLE) apparatus used in this work, shown in Figure 1, has been described in several previous publications [30][31][32], so not all details are described fully here, although modifications made since the previous publications are detailed. The technique employed was the static-analytic or analytical-isothermal method [33], where the vapour and liquid phases of a mixture in equilibrium at a known temperature and pressure are sampled and their compositions quantitatively analysed, in this case by gas chromatography (GC).…”
Section: Apparatusmentioning
confidence: 99%
“…Calibration of the GC system was performed in the manner described previously, employing the absolute-area method, the accuracy and effectiveness of which is well validated [30][31][32].…”
Section: Calibrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Fandinõ et al 11 reported vapor−liquid equilibrium data for CO 2 /H 2 and CO 2 /N 2 binary systems at temperatures between −55 and 30 °C at pressures ranging from the vapor pressure of CO 2 to approximately 15 MPa. Souza et al 12 carried out vapor−liquid equilibrium (VLE) measurements of a CO 2 /CH 4 binary system along seven isotherms at temperatures varying from just above the triple point to just below the critical point of CO 2 at pressures from the vapor pressure of pure CO 2 to approximately 9 MPa, as well as measurements of the three-phase solid−vapor−liquid equilibrium (SVLE) line at temperatures from approximately −67 to −57 °C. Lin et al 13 set up a VLE experimental apparatus based on the static analytic method to measure VLE data for the H 2 /CH 4 system at temperatures ranging from −173.2 to 142.5 °C and pressures below 3.5 MPa.…”
Section: Introductionmentioning
confidence: 99%